Barriers to the implementation of preconception care guidelines as perceived by general practitioners: a qualitative study - Mazza Danielle; Chapman Anna; Michie Susan (BMC, 2013)
Abstract Background Despite strong evidence of the benefits of preconception interventions for improving pregnancy outcomes, the delivery and uptake of preconception care and periconceptional folate supplementation remain low. General practitioners play a central role in the delivery of preconception care. Understanding general practitioners' perceptions of the barriers and enablers to implementing preconception care allows for more appropriate targeting of quality improvement interventions. Consequently, the aim of this study was to examine the barriers and enablers to the delivery and uptake of preconception care guidelines from general practitioners' perspective using theoretical domains related to behaviour change. Methods We conducted a qualitative study using focus groups consisting of 22 general practitioners who were recruited from three regional general practice support organisations. Questions were based on the theoretical domain framework, which describes 12 domains related to behaviour change. General practitioners' responses were classified into predefined themes using a deductive process of thematic analysis. Results Beliefs about capabilities, motivations and goals, environmental context and resources, and memory, attention and decision making were the key domains identified in the barrier analysis. Some of the perceived barriers identified by general practitioners were time constraints, the lack of women presenting at the preconception stage, the numerous competing preventive priorities within the general practice setting, issues relating to the cost of and access to preconception care, and the lack of resources for assisting in the delivery of preconception care guidelines. Perceived enablers identified by general practitioners included the availability of preconception care checklists and patient brochures, handouts, and waiting room posters outlining the benefits and availability of preconception care consultations. Conclusions Our study has identified some of the barriers and enablers to the delivery and uptake of preconception care guidelines, as perceived by general practitioners. Relating these barriers to a theoretical domain framework provides a clearer understanding of some of the psychological aspects that are involved in the behaviour of general practitioners towards the delivery and uptake of preconception care. Further research prioritising these barriers and the theoretical domains to which they relate to is necessary before a methodologically rigorous intervention can be designed, implemented, and evaluated.